Amplitude demodulation based on time-varying forced input of second-order oscillator circuit - Kittipute, K.; Koseeyaporn, J.; Wardkein, P. (My University, 2009)
In this article, a novel coherent amplitude demodulation based on time-varying force function of secondorder oscillator circuit and injection locking Phenomenon is proposed. The compactness of demodulation circuit is obtained because amplitude demodulation mechanism is inherent in one oscillator circuit. With injection locking property, frequency and phase of the oscillator is identical to that of the transmitted carrier. Based on time varying force function which is an AM signal, coherent demodulation is taken place. In laboratory experiment, the Colpitts oscillator at UHF band is employed where experimental results agree well with the proposed principle. ©2009 IEEE.
Keywords: Amplitude demodulation; Injection lock; Time-varying force function